Economic impact of thermal energy storage on natural gas power with carbon capture in future electricity markets - Markey, Ethan James, author; Bandhauer, Todd M., advisor; Quinn, Jason C., committee member; Herber, Daniel R., committee member (Colorado State University. Libraries, 2022)
As policies evolve to reflect climate change goals, the use of fossil fuel power plants in expected to change. Specifically, these power plants will need to incorporate carbon capture and storage (CCS) technologies to significantly reduce their carbon emissions, and they will be operated flexibly to accommodate the growing concentration of renewable energy generators. Unfortunately, most CCS technologies are very expensive, and they impose a parasitic heat load on the power plant, thereby decreasing net power output and the ability to operate flexibly. This research evaluated the economic potential of using hot and cold thermal energy storages (TES) to boost the net power output and flexibility of a natural gas combined cycle (NGCC) power plant with CCS capabilities. Resistively heated hot TES was used to offset the parasitic heat load imposed on the NGCC by the CCS unit while vapor compression cooled cold TES was used to chill the inlet air to the power plant. Thermodynamic models were created for the base NGCC + CCS power plant, the hot TES equipment, and the cold TES equipment, to determine key performance and cost parameters such as net power output, fuel consumption, emissions captured, capital costs, and operational costs. These parameters were then used to simulate the operation of the power plant with and without the TES technologies in accordance with fourteen electricity pricing structures predicted for different future electricity market scenarios. The difference in net present value (NPV) between the base NGCC + CCS power plant and power plant with the TES technologies was used as the primary economic metric in this analysis. The NPV benefit from increased revenue due to TES utilization was found to outweigh the NPV penalty from the additional capital costs. This positive economic result was attributed to the low cost of the TES equipment and the ability to charge the storages using cheap electricity from high levels of renewable output. The results have shown that hot TES increased NPV in 12 of 14 market scenarios while the cold TES increased NPV in 14 of 14 market scenarios. A combination of both hot and cold TES yielded the largest increases in NPV.
Keywords: natural gas combined cycle; carbon capture; thermal energy storage